El daño a la vida de relación en el Consejo de Estado (2016)
It seeks to cite the main concepts of damage to life relationship and its evolution, in the same way as the doctrine dealt with this kind of damage as jurisprudencialmente to come up in the Council of State, the different concepts since 1993 to 2014 being the period under study have emerged. With this research is intended to provide clarity to this concept and the relationship that it has within the tort ie a different damage that departs from moral damage, and thus specify when a victim may seek compensation for this type of injury.